Dinner for one : how cooking in Paris saved me - Dacres, Sutanya (Park Row Books, 2022)
"When Sutanya Dacres married her French boyfriend and moved to Paris at twenty-seven, she felt like she was living out her very own Nora Ephron romantic comedy. Jamaican-born and Bronx-raised, she had never dreamed she herself could be one of those American women in Paris she admired from afar via their blogs, until she met the man of her dreams one night in Manhattan. A couple of years later, she married her Frenchman and moved to Paris, embarking on her own "happily-ever-after." But when her marriage abruptly ended, the fairy tale came crashing down around her. Reeling from her sudden divorce and the cracked facade of that picture-perfect expat life, Sutanya grew determined to mend her broken heart and learn to love herself again. She began by cooking dinner for one in her Montmartre kitchen. Along the way, she builds Parisienne friendships, learns how to date in French, and examines what it means to be a Black American woman in Paris--all while adopting the French principle of pleasure, especially when it comes to good food, and exploring what the concept of self-care really means." -- inside front jacket flap.